Dual channel deep brain stimulation system (Kinetra) for Parkinson's disease and essential tremor: a prospective multicentre open label clinical study. Issue 3 (1st September 2002) - Vesper, J; Chabardes, S; Fraix, V; Sunde, N; Østergaard, K
Abstract : Objectives: To evaluate the safety and efficacy of a new dual channel stimulator (Kinetra) in patients with severe Parkinson's disease (PD) or essential tremor (ET). Methods: 111 patients with PD and 18 with ET were studied. Leads were implanted into the subthalamic nucleus (STN) or internal globus pallidus of patients with the akinetic/rigid type of PD. Leads were implanted into the ventral intermediate nucleus (VIM) of the thalamus or the STN in patients with the tremor dominant type of PD and in those with ET. Technical data on the device and adverse events occurring during the study were documented. Patients were assessed with established and validated clinical scales before surgery and at three and six months' follow up. Results: No device failure or unexpected adverse events occurred during the study. The dual channel stimulator used in stimulation of the STN, internal globus pallidus, and VIM in PD and ET was as safe and effective as the single channel stimulators in use. Mortality, morbidity, and infections were documented in the 129 treated patients. The parameter settings were similar to those usually programmed with single channel stimulators. Time spent in the operating room to implant the Kinetra system was systematically documented. In the PD group, improvement in the unified Parkinson's disease rating scale motor score, decrease in medication OFF periods, and reduced levodopa induced dyskinesia by bilateral STN stimulation were similar to those previously reported with bilaterally applied single channel stimulators. In the ET group upper and lower limb tremor scores were reduced by VIM stimulation. Activities of daily living improved in both disease groups. Conclusion: The Kinetra facilitated bilateral deep brain stimulation implantation surgery and is easy to use. It offers more advantages for the patient than the single channel stimulators; consequently, this new device may be recommended to treat patients with severe PD and ET.